Espace, codes et désir de transgression : l’impossible unité du Bel Inconnu - Marion Bonansea (Atalaya)
Renaud de Beaujeu, the author of Le Bel inconnu, an Arthurian romance in verse written at the end of the twelfth century, plays with the implicit conventions of the genre in his work. We here study this game in its treatment of enclosure: first, spatial enclosure that always leaves the hero dissatisfied on a diegetic level; then, narrative enclosure, because the conclusion of a romance is normally linked to the realization of a single homogeneous space. However, this has become impossible in Le Bel inconnu. The author thus tests formal limits of spaces and codes, and by obstructing the harmony desired in the courtly universe, maintains the desire of both the hero and the reader to fill the void.